ANALISA MIKROBIOLOGI MENGGUNAKAN NaCl SEBAGAI ALTERNATIF BUFFER PEPTONE WATER PADA PRODUK DESICCATED COCONUT DI PT. Unicoco Industries Indonesia - Angga Tritisari (PPPM POLTESA, 2023)
Microbiology is a science that studies very small living things that cannot be seen with the naked eye without the help of special equipment. These creatures are called microorganisms or microorganisms, but there are also harmful ones such as causing disease. Microbes consist of bacteria, fungi, and viruses. In general, each microbe has a different morphology and anatomical structure (Waluyo, 2004). Table salt or sodium chloride is used by humans for the food preservation process because it can inhibit the growth of bacteria. The purpose of this study was to determine the effect of variations in NaCl concentration on the number of bacterial colonies in Desiccated Coconut (DC) products. The type of research used is experimental with quantitative descriptive data analysis results. The sample used in this study was desiccated coconut with a concentration of NaCl as an alternative ingredient of Buffered Peptone Water (BPW) and the concentrations used were 0.80%, 0.85%, 0.90% and 0.95%. The results showed that all concentrations of NaCl could be used but at a concentration of 0.85% it was very close to the results with BPW control media for the total plate count, salmonella and yeast and mold tests.